2012
DOI: 10.3109/09273948.2012.674612
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis and Common Variable Immunodeficiency: Data from the DEF-I Study And Literature Review

Abstract: CVID can be associated with uveitis. Since uveitis can reveal the immunodeficiency, CVID diagnosis should be considered at the time of uveitis diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…A large population-based study in the Savoy area of France identified uveitis in four of 252 patients known to have CVID. 6 Most reported cases have had granulomatous features, including conjunctival granulomas, choroidal granulomas, and multifocal choroiditis. 7 Such granulomas are believed to develop as a result of CVID-associated immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…A large population-based study in the Savoy area of France identified uveitis in four of 252 patients known to have CVID. 6 Most reported cases have had granulomatous features, including conjunctival granulomas, choroidal granulomas, and multifocal choroiditis. 7 Such granulomas are believed to develop as a result of CVID-associated immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of corneal disease in patients with CVID are limited in the literature. These studies suggest that keratitis in CVID may manifest as infectious and/or inflammatory in nature [ 3 , 4 ]. Bilateral consecutive sterile corneal thinning that progressed to perforations was reported in a patient with CVID by Akpek et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of other ocular manifestations in CVID are also limited and include retinal vasculitis [ 4 ], uveitis [ 4 ], keratoconjunctivitis [ 5 , 6 ], and episodic retinal vein occlusions [ 7 ]. In several of these cases, initiation of treatment of IVIG and/or steroids led to the resolution of uveitis or granulomatous lesions [ 4 , 5 ] and recurrent keratoconjunctivitis [ 5 ]. Patients that have CVID may require lifelong immunoglobulin replacement to prevent further ocular and systemic manifestations of disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of ocular manifestations of granulomatous CVID, including granulomatous uveitis [18,19,20,21]. Autoimmune and non-granulomatous chronic inflammatory complications of CVID include uveitis, diffuse placoid chorioretinopathy, bird-shot chorioretinopathy, bilateral corneal ulcerations and orbital inflammations [22,23,24,25,26,27,28,29,30]. Starr et al [31 ]noted an unusual pattern of retinitis pigmentosa and CVID in one family.…”
Section: Discussionmentioning
confidence: 99%